Immunity to TBEV Related Flaviviruses with Reduced Pathogenicity Protects Mice from Disease but Not from TBEV Entry into the CNS - Petry, Monique; Palus, Martin; Leitzen, Eva; Mitterreiter, Johanna Gracia; Huang, Bei; Kröger, Andrea; Verjans, Georges M G M; Baumgärtner, Wolfgang; Rimmelzwaan, Guus F; Růžek, Daniel; Osterhaus, Albert; Prajeeth, Chittappen Kandiyil (Vaccines, 2021)
Tick-borne encephalitis virus (TBEV) is a leading cause of vector-borne viral encephalitis with expanding endemic regions across Europe. In this study we tested in mice the efficacy of preinfection with a closely related low-virulent flavivirus, Langat virus (LGTV strain TP21), or a naturally avirulent TBEV strain (TBEV-280) in providing protection against lethal infection with the highly virulent TBEV strain (referred to as TBEV-Hypr). We show that prior infection with TP21 or TBEV-280 is efficient in protecting mice from lethal TBEV-Hypr challenge. Histopathological analysis of brains from nonimmunized mice revealed neuronal TBEV infection and necrosis. Neuroinflammation, gliosis, and neuronal necrosis was however also observed in some of the TP21 and TBEV-280 preinfected mice although at reduced frequency as compared to the nonimmunized TBEV-Hypr infected mice. qPCR detected the presence of viral RNA in the CNS of both TP21 and TBEV-280 immunized mice after TBEV-Hypr challenge, but significantly reduced compared to mock-immunized mice. Our results indicate that although TBEV-Hypr infection is effectively controlled in the periphery upon immunization with low-virulent LGTV or naturally avirulent TBEV 280, it may still enter the CNS of these animals. These findings contribute to our understanding of causes for vaccine failure in individuals vaccinated with TBE vaccines.
Keywords: CNS; virus induced immunity; Langat virus; tick-borne encephalitis virus; neuronal damage